BASSON, WD Inventory of documents - BASSON, WD (ARCA, 2017)
Private papers of WD Basson on inter alia the National Party and the National Youth League
COVERAGE 1945-1958; 8 Files, photos and publications; 0,10 Metre.
Keywords: BASSON, WD; Inventories; Politicians; National Party